Paradigm-Specific Risk Conceptions, Patient Safety, and the Regulation of Traditional and Complementary Medicine Practitioners: The Case of Homeopathy in Ontario, Canada - Ijaz, Nadine (Frontiers in Sociology, 2020)
While the principle of risk reduction increasingly underpins health professional regulatory models across the globe, concepts of risk are neither static nor epistemically neutral. Conventional biomedicine’s risk conceptions are substantially rooted in principles of scientific materialism, while many traditional and complementary medicine systems have vitalistic epistemic underpinnings that give rise to distinctive safety considerations. The statutory regulation of traditional and complementary medicine providers has been identified by the World Health Organization as a strategy for enhancing public safety. However, complex risk-related questions arise at the intersection of medical epistemologies whose concepts are at best overlapping, and at worst incommensurable. Elaborating a theoretical concept of ‘paradigm-specific risk conceptions’, this work employs Bacchi’s poststructural mode of policy analysis (“What’s the Problem Represented to Be?”) to critically analyse risk discourse in government documents pertaining to the 2015 statutory regulation of homeopathic practitioners in Ontario, Canada. The Ontario government’s pre-regulatory risk assessments of the homeopathic occupation discursively emphasized cultural safety principles alongside homeopathy-specific risk conceptions. These paradigm-specific concepts, rooted in homeopathy’s epistemic vitalism, extend beyond materialist constructions of adverse events and clinical omission to address potential harms from homeopathic ‘proving symptoms’, ‘aggravation’ and ‘disruption’, all considered implausible from a biomedical standpoint. Although the province’s new homeopathy regulator subsequently articulated safety competencies addressing such vitalistic concepts, the tangible risk management strategies ultimately mandated for practitioners exclusively addressed risks consistent with the scientific materialist paradigm. This policy approach substantially echoes the implicit biomedical underpinnings evident in Ontario’s broader legislative context, but leaves a significant policy gap regarding the primary safety considerations originally articulated as substantiation for homeopath’s statutory regulation. To optimally preserve patient safety and full informed consent, regulators of traditional and complementary medicine professionals should favour a pragmatic, epistemically-inclusive approach that actively negotiates paradigm-specific risk conceptions from both biomedicine and the occupation under governance.